Silencing as a way to de-communise contemporary domestic social science - Berkov, Vladimir F. (Journal of the Belarusian State University. Sociology, 2022)
The idea is to consider the phenomenon of silencing as a way of decommunisation of modern Russian social science. The term «silencing» is absent in the methodological literature, so as a working definition is proposed to use the interpretation, which is given in the lexicographical dictionary S. I. Ozhegov, – as the implementation of aspirations, allowing by deliberate silence to hide, not to let know about something. The task is twofold: firstly, to present silence as a way to decommunicate the philosophical and methodological basis of modern domestic social science; second, to consider the use of this action on its subject-practical level. In the first case, it is proposed to demonstrate the fact that the silencing of the philosophy of Marxism as a methodology for studying social processes has had detrimental consequences, especially given the fact that this philosophy has been replaced by positivism (in the forms of postmodernism, poststructuralism, deconstructivism, etc.) which has 65 Знать, чтобы предвидеть... To Know so that to Foresee... long since become obsolete. Under the predominance of such «advanced» methodology, modern Russian social science and its branches have found themselves in a fundamental crisis. In fact, the attitude to cognition of deep cause-and-effect relations, correlation of essence and phenomena, necessity and contingency, possibility and reality and other is no longer obligatory. Methodological approaches that aspire to a non-subjective (objectivist) representation of reality have become dangerously popular. Secondly, by design, is to show that silencing has become a way of de-communising the subject-practical sides and levels of social science. In this connection, we should condemn the extremely poor use of information riches allowing to talk about the activity of the Communist Party of Belarus during the Great Patriotic War in various spheres of social life (in the educational process, in educational and propaganda work, in the training of scientific-pedagogical personnel). The exceptional importance of objective and full coverage of Communist Party history (the All-Union Communist Party of Bolsheviks and its part) for educating young people in the spirit of patriotism, for exposing the rewriting of history by Western proponents of de-communisation, for solving the urgent problems of preventing the reduction of Communist ideology, its withdrawal from it and thus strengthening the bourgeois (liberal, in the current terminology) ideology, should be emphasised.
Keywords: silencing; de-communisation; modern domestic social science; Marxist methodology; positivism; Communist Party of Belarus